(untitled) (Journal of Universal Excellence, 2026)
Research question (RQ): What is the prevalence of incontinent patients in acute hospital settings? How do staff choose incontinence devices for patient care? Purpose: The purpose of the study is to find out what proportion of incontinent patients are managed in acute hospital settings and to find out what incontinence devices are used by staff to care for incontinent patients and how. Based on the findings, we want to implement measures to improve the quality of care for patients with incontinence. Method: We used a descriptive method to review the literature, developed a questionnaire for data collection, trained staff on how to conduct the survey, and measured the point prevalence of incontinence using a cross-sectional survey. Results: Slightly more men (51.6%) than women (47.3%) were included in the survey, and for 1.1% of the patients, gender information was not available. Of the 1,277 patients included in the study, 750, or a good half (58.7%), were continent and did not use incontinence devices. A further 83, or 6.5%, were continent and used incontinence devices. 31.1% or 397 patients were incontinent and used incontinence devices, while 17 or 1.6% did not, despite being incontinent. For 2.3% of patients, no information was available. The point prevalence was 32.4%. Organisation: Good organisation is essential for good quality care for incontinent patients, so it is important to improve the quality of care for incontinent patients based on the findings. Society: Adequate patient awareness of incontinence is of paramount importance for the reduction and management of incontinence in the population. Originality: This is the first study in Slovenia to report the prevalence of incontinence in acute hospital settings. Limitations/follow-up research: The survey was conducted in a single tertiary care institution; we recommend that such a survey be conducted in the remaining hospitals in Slovenia.